1996
DOI: 10.1111/j.0022-3646.1996.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

BIOENERGETIC PROCESSES ARE MODIFIED DURING NITROGEN STARVATION AND RECOVERY IN PHORMIDIUM LAMINOSUM (CYANOPHYCEAE)1

Abstract: In the non‐N2‐fixing cyanobacterium Phormidium laminosum (Agardh) Gomont (strain OH‐I‐pCl1), N starvation induced an increase in the rate of respiration and a decrease in the rate of O2 evolution. When NO3− was added to illuminated N‐starved cells, O2 evolution immediately increased to levels shown by NO3− grown cells, even though N‐starved cells had lost most of their in vitro photosynthetic activities. Stimulation of noncyclic electron flow was maximal under light‐saturating conditions and after 2–3 days of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…In such cyanobacteria, phycobilisome degradation under nitrogen-limited conditions can provide an intracellular source of nitrogen, and reduce both photodamage and oxygen evolution Ochoa de Alda et al, 1996;Sauer et al, 2001). In Synechococcus sp.…”
Section: Introductionmentioning
confidence: 99%
“…In such cyanobacteria, phycobilisome degradation under nitrogen-limited conditions can provide an intracellular source of nitrogen, and reduce both photodamage and oxygen evolution Ochoa de Alda et al, 1996;Sauer et al, 2001). In Synechococcus sp.…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike P. laminosum, the intracellular content of amino acids in other cyanobacteria did not change appreciably after the NH,+ pulse, except that of glutamate and glutamine (Rowell et al 1977, Flynn and Gallon 1990, Mkrida et al 1991, Coronil et al 1993. Recently, we observed that the addition of NO,or NH,+ to N-starved cells of P. laminosum resulted in a large stimulation of amino acid biosynthesis, the effect being faster and greater when NH,+ was assimilated (Tapia et al 1996b).…”
Section: Discussionmentioning
confidence: 88%
“…These effects depend on experimental conditions and the N nutrition of the cells. Under most conditions, assimilation of either NO,-or NH4+ induces an increase in carbon flow to amino acids and their oxoacid precursors at the expense of reserve carbohydrates (Lawrie et al 1976, Bassham et al 1981, Tapia et al 1996b). In addition to this general depressive effect of N assimilation on carbon flow to glycogen, degradation of glycogen appears to be stimulated by NH,+ assimilation at low (but not at high) irradiance (Garcia-Gonz5lez et al 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is expected that light maintains the PQ pool more reduced in NH4-grown than in NOrgrown cells. On the other hand, at the light intensities used to maintain N-starved cultures (i,e,, 33 timol m~^ s*'), the excitation of PSII was negligible, whereas that of PSI occurred as in N-sufftcient cells (Ochoa de Alda et al, 1996), This suggests that the PQ pool is even more oxidized in Nstarved cells than in N sufficient ones. Short-term changes in photosynthetic apparatus Short-term, NO; addition to N-starved cells and NHJ addition to NOi-grown or N-starved cells stimulated the respiration rate in the dark (Fig, 6), As in algae (Mohanty et al, 1991), this correlated with a state 2 transition, suggesting a reduction of the PQ pool.…”
Section: Discussionmentioning
confidence: 98%